CITRA DIRI SEORANG DA’I DI MEDIA SOSIAL - Selly Oktaviani (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2019)
Social media as a medium of information and public communication at this time, became a medium of propaganda for preachers to deliver their propaganda widely. People who need a self-image that can get people and their preaching can be easily accepted by the community (mad’u). How does a preacher break his image involved in social media, how the preacher prepares the image before Mad’u (the area behind the stage), how the preacher displays the image before Mad’u (front stage area), and How Da’i denied his popularity in the community as a trust from what should be opposed to him in the mass media (out of the regional stage) into the formulation of the problem in this study. A preacher uses a variety of ways so that the purpose of his da’wah is successful. Self-image is used to attract the attention of the target of the Da’wah (mad’u). Before dealing with mad’u for da’wah, a preacher made some preparations to present a self-image that was confirmed before mad’u. Remember the full meaning of belief in him. Convincing self-image approved by the preacher, it will give a positive impression also by mad’u. Convincing here, it can be seen from the attitudes, clothes, and sayings of the preacher. A preacher needs that trust to succeed in carrying out his da’wah. In addition, the preacher also received various benefits both material and immaterial obtained.